Team, Front cover, Editorial information, Table of Content, Back Cover - Journal Editor (Jurnal Sains dan Kesehatan, 2015)
Jurnal Sains dan Kesehatan. 2015. Volume 1 Nomor 1. Front cover, Editorial information, Table of Content, Back Cover